Legal Effectiveness and Gaps in ODGJ Protection: Rights and Maqāṣid Analysis - Dinda Zilfattisa Kusnan; Zamroni Abdussamad; Fitran Amrain; Akmal Hidayah Halim (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study aims to analyze the disharmony between normative regulation and the implementation of the protection of Persons with Mental Disorders (ODGJ) in Indonesia, especially at the regional level, by integrating the perspectives of national law, human rights, and Islamic law. The method used is normative legal research (doctrinal legal research) enriched with a socio-legal approach. The research approach includes the statute approach, conceptual approach, and case approach, with theoretical frameworks in the form of legal functionalization theory, legal protection theory, and maqāṣid al-syarī'ah which emphasizes the protection of the soul (ḥifẓ al-nafs) and the principle of non-discrimination. The results of the study show that the failure of ODGJ protection does not stem from weaknesses in legal norms, but from structural failures in implementation. The disharmony of regulations is reflected in weak coordination between agencies, limited resources for mental health workers, and the lack of operational and applicable regional regulations. In addition, the legal culture of the community that is still full of stigma and discrimination exacerbates the ineffectiveness of legal protection for ODGJ. This study concludes that the effectiveness of ODGJ protection requires an integrative model that incorporates a human rights approach and the values of maqāṣid al-syarī'ah in an implemented manner. The main findings confirm that the main problem lies in structural and cultural aspects, not normative; Therefore, it is recommended to strengthen implementing regional regulations, increase institutional capacity and mental health services, and social interventions based on public education to remove stigma, in order to realize an inclusive, effective, and equitable ODGJ protection system.